Applying nondestructive testing to quality control of additive manufactured parts - Aleshin, N. P.; Grigor’ev, M. V.; Shchipakov, N. A.; Prilutskii, M. A.; Murashov, V. V. (Russian journal of nondestructive testing, 2016)
Possibilities, application domains, advantages, and limitations are considered for currently used physical methods of nondestructive testing of additive manufactured parts. The methods are classified according to the physical principle of operation.